Digital Resources of "Floor to Ceiling" Tasks - Flick, Michael; Kuchey, Debbie (Ohio Journal of School Mathematics, 2019)
The authors elaborate upon the National Council for Teachers of Mathematics' standards and describe how mathematical rich tasks found on various websites can help support those standards. The authors describe many of these websites and what they have to offer to teachers and students.